Part III: Short Papers from the Course. Issue 6 (18th August 2019) - Dobson, Marcia D-S.; Riker, John H.
ABSTRACT: At the end of each class, we ask students to write either an annotated bibliographic essay on a psychoanalytic subject of their choosing or a short paper. We include here three examples of the kind of work we receive. The first is an annotated bibliography written by Monica Black, a drama major, who has been "play-acting" since childhood and who is now a serious actress, exploring the question of "Why Perform?" She wrote the paper when she was a sophomore. The second is written by Becca Stine, a junior creative writing major, who, when she saw Waiting for Godot at the Chicago Shakespeare Theater, had moving insights about her relation with her sister, insights that were enhanced by the psychoanalytic reading we did in relation to the drama. The third, by first-year neuroscience major Peter Lehman, is an annotated bibliography that seeks to understand how neurobiology and psychoanalysis can best intersect.